PENGEMBANGAN WEB COMPANY PROFILE TERINTEGRASI DENGAN API WHATSAPP (STUDI KASUS: AGEN SEMBAKO AL-BARKAH) - Abidatul Izzah (INFOTECH journal, 2021)
Today, in the era of Marketing 5.0, sell business using technology are highly recommended. The owner of the Al-Barkah groceries agent in Kediri-East Java is one of the entrepreneurs who use social media information technology such WhatsApp. However, the problems encountered is the limited feature of stories on WhatsApp so that it cannot optimally accommodate wider marketing to the public. Therefore, it is a needed a media that can store information on Al-Barkah products and also can be seen without a duration of time. This media is also expected to be connected with WhatsApp that has been used for marketing before. Thus, this study aims to develop a website containing business information or what is popular as a Company Profile. Furthermore, it is also integrated with WhatsApp social media. Then, system development stages start from system requirements analysis, design, implementation in programming, and system testing. The result of this research is a company profile web-based that has been tested according to the designed functional requirements.